Exotic Clinic Karawang's Marketing Strategy in Increasing Consumer Attraction to the Programcontouring, Slimming, and Anti-Aging - Riyan Andika Y; Endang Komara; Oke Oke Andikarya (Research of Service Administration Health and Sains Healthys, 2025)
This study aims to analyze Exotic Clinic Karawang's marketing strategy in increasing consumer appeal for its contouring, slimming, and anti-aging programs. The clinic faces challenges in maintaining a consistent number of patients amid fierce competition in the aesthetic industry. The study uses a qualitative case study approach with data collection through in-depth interviews, participatory observation, and documentation studies. The research focuses on the implementation of the marketing mix (7P): product, price, place, promotion, people, process, and physical evidence. The results show that Exotic Clinic has made various efforts, such as providing quality services, adjusting prices, improving location accessibility, and utilizing digital media for promotion. However, there are obstacles such as suboptimal communication strategies, limited human resources in implementing digital promotion, and consumer perceptions that are not yet fully formed regarding service excellence. Supporting factors for success include the clinic's reputation, the competence of medical personnel, and adequate physical facilities. This study provides practical contributions for Exotic Clinic to strengthen more targeted marketing strategies, as well as theoretical contributions to the study of healthcare service marketing. Recommendations include enhancing digital promotional activities, improving patient experience, and conducting ongoing evaluations of implemented marketing strategies to increase consumer loyalty and interest in repeat visits.